RATIONAL APPEAL VS EMOTIONAL APPEAL IN FORMING CONSUMER’S INTEREST THROUGH ADVERTISEMENT - Pramatatya Resindra Widya (Department of Management - Institut Shanti Bhuana, 2019)
The aim of this study is to examine the impact of emotional appeal advertisement in television and rational appeal advertisement in magazine to customer’s purchase intention. Data were collected using purposive sampling for 100 people and analyzed using multiple regressions. The finding of research is that emotional-appeal advertising in television has less impact on customer’s purchase intention because of switching behavior during commercial break. While the rational appeal advertisement has significant impact on customer’s purchase intention because they have enough time to think and analyze the information in the advertisement.